Legal Facts in Legal Opinions Formulation on The Decisions of Islamic Civil Case - Ahmad Muqorobin; May Shinta Retnowato; Nur Helmy Iffah Wafiyah (Veteran Law Review, 2023)
Development of Islamic civil cases today, the problems that arise in society are increasingly complex and the public's need for services in the legal field is getting higher. This does not escape the need for legal opinions from experts such as lawyers, advocates, or legal advisors. This legal opinion is what we often call a legal opinion. In practice, the determination of a punishment must be fair. To realize this justice, the law enforcers should be impartial and consider many things before deciding on a sentence or giving a legal opinion. The weighing of these decisions can be done by looking at the facts that happened and studying them, presenting witnesses, and so on. Legal facts are one of the processes that cannot be overlooked by persons investigating a case, because if this process is missed or not thorough enough, it can affect a decision. The method used in this study is a qualitative juridical normative method. This study aims to find out that legal facts will affect the decisions of Islamic civil law that will be taken and legal opinions that will be made by a legal expert. The result of the study is that Legal facts are important to note because the discovery and analysis of legal facts can support and complete the clauses that will be included in the legal opinion and the decisions that will be handed down by the judge on the defendant. Although in the civil law rules there is no information about the importance of legal facts in legal opinions, if viewed from the facts that occur, it can be identified as a legal risk that will be accepted by the client.